Extraction and Analysis of Xylitol in Sugar-Free Gum Samples by GC-MS with Direct Aqueous Injection - Suranga M. Rajapaksha; Katherine Gerken; Todd Archer; Patty Lathan; Achala S. Liyanage; Deb Mlsna; Todd E. Mlsna (Journal of Analytical Methods in Chemistry)
Xylitol, a sugar substitute frequently used in sugar-free gum, is generally considered harmless to humans but it can be extremely toxic to dogs. Dog-owning customers are becoming increasingly aware of the risks associated with xylitol-containing chewing gums. However, there remains some uncertainty if these chewing gums are still dangerous to dogs after they have been partially consumed. In this work, a reliable low-cost analytical method has been developed to quantify the xylitol in sugar-free gum samples. Xylitol was extracted from gum samples using water as a solvent. Extractions were analyzed by GC-MS with direct aqueous injection (DAI). This method was successfully applied to over 120 samples including fresh gum and 5 min, 15 min, and 30 min chewed gum samples.